Endowment-funding: socio-economic nature, operational dynamics and the possibility of extrapolating it to the domestic environment - Khussainova, Zh.S.; Assanova, M.K.; Mardanova, A.T.; Petrenko, E.S.; Abauova, G.M. (BUKETOV BUSINESS REVIEW, 2021)
Objective: identification of the nature, features, modern mechanism and factors of operational dynamics of endowment funding in the world economy and its primary registration in the domestic environment. Methods: A wide range of system, structural, and comparative analysis methods are used. Results: The parameters of the socio-economic nature of endowment funding, the general model of its functioning are identified, the range of modern applied tools for its development in the world economy and the features of its formation in the domestic environment are outlined. Conclusions: The competitiveness of modern society depends on the multifactorial mechanism of social and economic communications. A special role is played by the qualitative modernization of human capital, the growth of its professional and social competencies. And therefore, the change in the appearance of higher education, which forms the basis for the post-industrial environment, the discovery of scientific innovations is relevant. In this regard, endowment funding is becoming one of the sources of the evolution and activation of university education. Moreover, in developed countries with a long history of its evolution, dynamic factors, new financial forms of accumulation of funds in endowment funds, expansion of options for evaluating the effectiveness and involvement of subjects in the system of endowment fund donors are diversifying. In domestic conditions, only the contours of institutional norms and immature endowment funding are being created. Therefore, the theoretical and practical layers of the analysis of the essential nature of endowment funding, the trends of its evolution in the subjective and instrumental terms for the implementation of the model of additional financing of universities in domestic conditions are updated. Acknowledgments: This research is funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AP09562829)